2006
DOI: 10.1038/sj.bjc.6603453
|View full text |Cite
|
Sign up to set email alerts
|

Desmocollin switching in colorectal cancer

Abstract: The desmocollins are members of the desmosomal cadherin family of cell -cell adhesion molecules. They are essential constituents of desmosomes, intercellular junctions that play a critical role in the maintenance of tissue integrity in epithelia and cardiac muscle. In humans, three desmocollins (Dsc1, Dsc2 and Dsc3) have been described. The desmocollins exhibit tissue-specific patterns of expression; only Dsc2 is expressed in normal colonic epithelium. We have found switching between desmocollins in sporadic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 16 publications
3
78
1
Order By: Relevance
“…We know that in the majority of colon cancers, DSC2 gene expression is lost, with the concomitant induction of DSC1 and DSC3 expression (7). We can speculate that the switch to DSC1 and DSC3 may foster EMT and an invasive phenotype.…”
Section: The Regulation Of the Dsc2 Gene May Provide Insights Into Dementioning
confidence: 99%
See 1 more Smart Citation
“…We know that in the majority of colon cancers, DSC2 gene expression is lost, with the concomitant induction of DSC1 and DSC3 expression (7). We can speculate that the switch to DSC1 and DSC3 may foster EMT and an invasive phenotype.…”
Section: The Regulation Of the Dsc2 Gene May Provide Insights Into Dementioning
confidence: 99%
“…However, in several human cancers, there is a breakdown in this tissue-restricted expression pattern. It is believed that this ''desmocollin switching'' could be a component of EMT, similar to the well-described ''cadherin switching'' (6,7). The mechanisms regulating this change in desmocollin gene patterning are not known, although the switch from E-cadherin to N-cadherin seen with EMT is brought about by potent transcriptional repressors such as Slug or Snail that suppress E-cadherin gene expression (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, the immunohistochemistry data are contradictory and this may be at least in part due to the use of antibodies in early studies that do not distinguish between the various desmocollin and desmoglein gene products. Recent studies have shown loss of Dsg2 in gastric cancer (Biedermann et al, 2005;Yashiro et al, 2006), Dsc2 in colorectal cancer (Khan et al, 2006) and Dsc3 in breast cancer (as a result of promoter hypermethylation) (Oshiro et al, 2005). By contrast, Dsg2 and Dsg3 are overexpressed in squamous cell cancer of the skin (Kurzen et al, 2003) and head and neck cancer (Chen et al, 2007), respectively.…”
Section: Other Desmosomal Constituents Wnt/b-catenin Signalling and mentioning
confidence: 99%
“…Along the same lines, DSC2 and DSC3 expression is downregulated in colorectal and breast cancer, respectively [44,45]; whereas DSG3 is overexpressed in squamous cell carcinoma and head and neck cancer [43,46]. In general, whether desmosomes are involved in cancer and metastasis is very poorly understood [47].…”
Section: Desmosomes and Cancermentioning
confidence: 99%